Decoding the Genetic Enigma: A Case Study on Congenital Anomalies with Developmental Delay and 9q Duplication Unveiled Via Comprehensive Whole Exome Sequencing and Cytogenetic Analysis: Unraveling 9q Duplication Via Comprehensive Whole Exome Sequencing - Dehghanzad, Reyhaneh; Aghajanpour Mir, Mohsen; Golchehre, Zahra; Asadollahi, Mostafa; Rahbar Parvaneh, Roghayeh; Tasharrofi, Behnoosh; Shakoori Farahani, Abbas; Keramatipour, Mohammad (Iranian Journal of Child Neurology, 2026)
Objectives: Approximately 3% of newborns worldwide are affected by Congenital Anomalies (CAs) with or without Intellectual Disability (ID)/Developmental Delay (DD), often caused by genetic factors such as single-gene disorders or chromosome aberrations. Whole Exome Sequencing (WES) has become a highly effective first-tier test for identifying these genetic factors, detecting both Copy Number Variations (CNVs) and Single Nucleotide Polymorphisms (SNPs)/Insertion/Deletion Polymorphisms (INDELs), while conventional cytogenetic analysis can provide additional valuable information to confirm results where applicable. Materials & Methods: The proband DNA was extracted and subjected to WES. Genetic variants were analyzed using the Genome Analysis Toolkit (GATK) following the American College of Medical Genetics and Genomics (ACMG) guidelines. Additionally, karyotyping of the child and her parents was conducted with high-resolution CTG banding after harvesting conventional cell cultures and performing Giemsa banding on metaphase spreads of cultured leukocytes. Results: This study describes a patient with microcephaly, mild intellectual disability, and specific facial features, where initial WES did not identify any causative SNPs/INDELs. However, subsequent WES-based analysis for CNVs revealed the presence of dup (9) (q21.11q22.32). Further chromosomal analysis uncovered unique karyotypes for the patient [46, XX, t (5; 9) (p15.1; q22.1), add (14) (p11.1)] and her father [46, XY, t (5;9)(p15.1;q22.1)], and a normal karyotype for the mother. Conclusion: The present study confirms the effectiveness of utilizing WES-based analysis of CNVs and SNPs/INDELs as the primary diagnostic test for identifying patients with CAs/ID/DD.